Korelasi Keinginan Bunuh Diri dengan Hierarki Kebutuhan Maslow dalam Film “Kembang Api” Karya Herwin Novianto - Khotima, Nurul Ashyfa; Syihabuddin, Syihabbudin (Asosiasi dosen IDEBAHASA KEPRI, 2023)
This research aims to analyze the psychological conflicts of the four characters in the film